Musculoskeletal MRI at 3.0T and 7.0T: A Comparison of Relaxation Times and Image Contrast - Jordan, Caroline D. (2011)
OBJECTIVE: The purpose of this study was to measure and compare the relaxation times of musculoskeletal tissues at 3.0T and 7.0T, and to use these measurements to select appropriate parameters for musculoskeletal protocols at 7.0T. MATERIALS AND METHODS: We measured the T(1) and T(2) relaxation times of cartilage, muscle, synovial fluid, bone marrow and subcutaneous fat at both 3.0T and 7.0T in the knees of five healthy volunteers. The T(1) relaxation times were measured using a spin-echo inversion recovery sequence with six inversion times. The T(2) relaxation times were measured using a spin-echo sequence with seven echo times. The accuracy of both the T(1) and T(2) measurement techniques was verified in phantoms at both magnetic field strengths. We used the measured relaxation times to help design 7.0T musculoskeletal protocols that preserve the favorable contrast characteristics of our 3.0T protocols, while achieving significantly higher resolution at higher SNR efficiency. RESULTS: The T(1) relaxation times in all tissues at 7.0T were consistently higher than those measured at 3.0T, while the T(2) relaxation times at 7.0T were consistently lower than those measured at 3.0T. The measured relaxation times were used to help develop high resolution 7.0T protocols that had similar fluid-to-cartilage contrast to that of the standard clinical 3.0T protocols for the following sequences: proton-density-weighted fast spin-echo (FSE), T2-weighted FSE, and 3D-FSE-Cube. CONCLUSION: The T(1) and T(2) changes were within the expected ranges. Parameters for musculoskeletal protocols at 7.0T can be optimized based on these values, yielding improved resolution in musculoskeletal imaging with similar contrast to that of standard 3.0T clinical protocols.